Penerapan Metode Design Thinking Dalam Pembuatan UI/UX Aplikasi Marketplace Ikan Hias - Mochammad Nabil Nugraha Ramadhan; Nur Cahyo Wibowo; Eka Dyar Wahyuni (Router : Jurnal Teknik Informatika dan Terapan, 2024)
The ornamental fish market is growing rapidly due to the great interest in the hobby of keeping ornamental fish which is supported by technological advances.  Unfortunately, these technological advances also include problems that are still experienced by sellers and buyers, such as a lack of understanding of how to send fish and a lack of information about trustworthy sellers.  This research aims to formulate user needs and create an ornamental fish marketplace application interface using the Design Thinking method with good usability values.  This research discusses creating application interface designs using the Design Thinking method which focuses on users to overcome the problems above.  This research produces interface designs for 21 features with the main feature being a community that makes it easier for sellers to interact and displays ratings on stores to make it easier to find trustworthy sellers.  This research was carried out in two iterations, with the final test results in the second iteration being 92.85% (Learnability value) and 91.15% (Efficiency value) for five sellers.  Test results for five hobbyists / potential buyers obtained a Learnability score of 97.14% and Efficiency of 92.72%.  Meanwhile, Satisfaction (SUS) for both got a score of 83.5%.  The test results produced a good usability design.